Clinical Pharmacogenetics Implementation Consortium Guideline for CYP2D6 and CYP2C19 Genotypes and Dosing of Tricyclic Antidepressants. Issue 5 (16th January 2013) - Hicks, J K; Swen, J J; Thorn, C F; Sangkuhl, K; Kharasch, E D; Ellingrod, V L; Skaar, T C; Müller, D J; Gaedigk, A; Stingl, J C
<x xml:space="preserve">Abstract</x> Polymorphisms in CYP2D6 and CYP2C19 affect the efficacy and safety of tricyclics, with some drugs being affected by CYP2D6 only, and others by both polymorphic enzymes. Amitriptyline, clomipramine, doxepin, imipramine, and trimipramine are demethylated by CYP2C19 to pharmacologically active metabolites. These drugs and their metabolites, along with desipramine and nortriptyline, undergo hydroxylation by CYP2D6 to less active metabolites. Evidence from published literature is presented for CYP2D6 and CYP2C19 genotype–directed dosing of tricyclic antidepressants. Clinical Pharmacology & Therapeutics (2013); 93 5, 402–408. doi:10.1038/clpt.2013.2